Compatibility of plastics with cytotoxic drug solutions: comparison of polyethylene with other container materials - Beitz, Christoph; Bertsch, Thomas; Hannak, Dieter; Schrammel, W.; Einberger, Claus; Wehling, Martin (International journal of pharmaceutics, 1999)
In this study low density polyethylene (LDPE)-containers were compared to glass bottles and polyvinyl chloride (PVC) bags in view of adsorption effects with antineoplastic drugs. The infusion containers were supplemented with therapeutic doses of the nine common cytotoxic drugs carboplatin, carmustine, cytarabine, dacarbazine, fluorouracil, gemcitabine, melphalan, methotrexate and vinorelbine. 0.9% isotonic sodium chloride solution and 5% dextrose served as infusion solutions. The containers were stored at room temperature or at 4°C, protected from light, for periods of up to 168 h. Turbidity, change of colour and visible crystallization were not observed. Samples were collected at different time intervals and drug contents were determined with high-performance liquid chromatography (HPLC). Preparations of carmustine showed no adsorption phenomena when stored in LDPE or in glass at 4°C. At room temperature in LDPE, a slight decrease in concentration due to adsorption was monitored. However the drug loss in PVC bags was greater. Dacarbazine and melphalan showed decreases in concentration, which were independent on the type of container material. The remaining analyzed agents showed no drug loss at all. In conclusion, investigated drugs were stable in all three container types, with the best stability in glass bottles, followed by LDPE and PVC.
Gesehen am 13.10.2022